6-3(a-1)=1+a

Simple and best practice solution for 6-3(a-1)=1+a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-3(a-1)=1+a equation:


Simplifying
6 + -3(a + -1) = 1 + a

Reorder the terms:
6 + -3(-1 + a) = 1 + a
6 + (-1 * -3 + a * -3) = 1 + a
6 + (3 + -3a) = 1 + a

Combine like terms: 6 + 3 = 9
9 + -3a = 1 + a

Solving
9 + -3a = 1 + a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1a' to each side of the equation.
9 + -3a + -1a = 1 + a + -1a

Combine like terms: -3a + -1a = -4a
9 + -4a = 1 + a + -1a

Combine like terms: a + -1a = 0
9 + -4a = 1 + 0
9 + -4a = 1

Add '-9' to each side of the equation.
9 + -9 + -4a = 1 + -9

Combine like terms: 9 + -9 = 0
0 + -4a = 1 + -9
-4a = 1 + -9

Combine like terms: 1 + -9 = -8
-4a = -8

Divide each side by '-4'.
a = 2

Simplifying
a = 2

See similar equations:

| 4.4s+6.2=8.85s-1.8 | | 2+3w=5 | | (w+3)7= | | 16x-1=11x-21 | | 4x+39=x+15 | | p^2+9p+14=0 | | 11+5=-4(4x-4) | | 2x^2-13x-24=0 | | 3c+2.5= | | .6x-0.8x+2=-2 | | (14x^5+7x^3+x)-(x+20)(2nx^2+1)=14x^5-15x^3-440x^2-20 | | -x+8=25 | | X+48=5x | | x+1=2x+2 | | I=112X-223628 | | 2(3t+5)-4(2t-1)=6 | | 6x-360=0 | | 3x+45=12x | | 9j+34j= | | 24x-360=0 | | (3x-1)(2x+5)=0 | | -27=-2+5w | | 8x^2=26x | | (3x+1)(2x-5)=0 | | 14x^2=21x | | 15x^2y-3xy^2=0 | | 6+5x+4x+1=12x+1 | | 4.9t^2-1960t=0 | | 14x^2-28x+14=0 | | (5m-2)(m+3)= | | 27(.33)+8y=25 | | 5x+1=2x+25 |

Equations solver categories